Tracing the Quality of the Sanad in Hadith Learning Using al-Maktabah al-Shāmilah Application: Menelusuri Kualitas Sanad Dalam ‎Pembelajaran Hadith Menggunakan ‎Aplikasi al-Maktabah al-Shāmilah - Akbar, Dzulfikar; Handayani, Puspita (Procedia of Social Sciences and Humanities, 2024)
The emergence of Information and Communication Technologies (ICTs) has transformed the paradigm of contemporary education, including Islamic Studies. The use of e-learning and digital libraries (DL) allows access to books and journals online, which were previously only available in print form in libraries. One important DL application in Islamic Studies is Al-Maktabah As-Shamilah (MS), which provides thousands of Arabic books for free. This application efficiently facilitates the exploration of Islamic literature, including hadith and the science of Jarh̟ wa t-Ta’dīl (JT). However, its utilization requires a good command of the Arabic language.In Indonesia, the teaching of Ulumu l-Hadith at the university level faces challenges related to students' Arabic language proficiency. Therefore, the Problem-Based Learning (PBL) method is implemented to enhance students' understanding of evaluating hadith narrators' quality.